Tingkat Bagi Hasil Mudharabah Bank Umum Syariah: Analisis Kinerja Keuangan - Kurniawan, Fakhry Hafiyyan; Nugraha, Nugraha; Maulana, Mahbub Afini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to examine the signaling theory by analyzing the effect of financial performance such as profitability, financing risk, liquidity, operational efficiency and capital adequacy on the profit sharing rate of Islamic Commercial Banks (BUS) mudharaba deposits. The method used in this research is a quantitative descriptive method with panel data regression analysis techniques. Data collection techniques were carried out through documentation and literature study methods. The population in this study were 14 Islamic Commercial Banks. The method used for sampling in this research is purposive sampling with predetermined criteria, with a total sample of 11 Islamic Commercial Banks for four years (2017-2020), with a total of 176 observational data. The results showed that simultaneously the level of profitability, the level of financing risk, the level of liquidity, the level of operational efficiency and the level of capital adequacy had a significant effect on the rate of profit sharing for mudharaba deposits. Partially, the level of profitability and the level of operational efficiency have a positive and significant effect on the rate of profit sharing for mudharaba deposits. The level of liquidity has a negative and significant effect on the rate of profit sharing for mudharaba deposits. The level of financing risk and the level of capital adequacy have no effect on the rate of profit sharing for mudharaba deposits.